Análisis de la aplicación de nuevas tecnologías de información en la modalidad semipresencial de la Universidad Estatal de Milagro - Pacheco Olea, Fernando (2015)
The potential that new information technology provide to the university teacher and to the society through the use of technological tools supply rapid processing of information exchange and transformation in their academic future. The application of these tools is very useful for the teachers of the millennium because technological advances provide an important contribution to the development of their classes. The use and application of new technology must be harnessed to achieve continuous learning, distance learning and learning under the control of learners in order to solve challenges and problems that occur in a less developed society. Notably any change brings resistance, the anxiety in teachers when they try to implement ICT tools influence their work whereas they see a host of constraints that leads them to decline to continue their updating because they do not possess the technological innovation culture and see themselves affected in their professional lives. As such, this paper aims to raise awareness of the teaching-learning process of teachers participating in the blended system at Milagro State University, strengthening the use of technological tools to prompt students’ motivation in the different stages of study.